Transcriptome analysis identifies EDA1 variants disrupt FOSB-mediated regulation of odontogenic epithelial cell behaviors during dental germ development - Zhang, Jing; Kong, Xuanting; Yuan, Yunyun; Zhao, Ya; Ding, Yulin; Ren, Jiabao; Shen, Wenjing (Frontiers in Cell and Developmental Biology, 2026)
Here, we systematically investigated the effects of EDA1 variants on apoptosis, migration, and adhesion in ameloblast-like LS8 cells and identified downstream effectors of the EDA-NF-κB pathway through RNA sequencing (RNA-seq) combined with in vivo and in vitro validation. LS8 cells were transiently transfected with four constructs: wild-type (Wt) EDA1, nonsyndromic tooth agenesis-associated EDA1 variant (EDA1-A259E), X-linked hypohidrotic ectodermal dysplasia-associated EDA1 variant (EDA1-H252L), or empty vector control (pCMV-C-FLAG). We used flow cytometry, wound-healing assay, and cell counting kit 8 assay to assess cell apoptosis, migration, and adhesion, respectively. High-throughput RNA-seq was used to identify differentially expressed genes, which were subsequently validated through quantitative polymerase chain reaction and immunoblotting. Spatiotemporal Fosb expression patterns were comparatively analyzed in Wt and Tabby mouse tooth germs through in situ hybridization by using RNAscope. Wt EDA1 transiently enhances cellular migratory capacity, a function compromised in the pathogenic EDA1 variants. The EDA-NF-κB pathway operates through FOSB-mediated transcriptional regulation, as evidenced by coordinated suppression of Fosb expression at transcriptional and translational levels in the mutant models. Therefore, FOSB is a candidate downstream effector in EDA1-mediated odontogenesis. These results provide mechanistic insights into ectodermal dysplasia pathogenesis.